Conductive copper paste and laser sintering process thereof
By utilizing the self-oxidation and reduction of copper ligands to generate conductive copper paste with nano-copper crystal nuclei in an air atmosphere, the problem of copper powder oxidation was solved, achieving efficient laser sintering in an air atmosphere, reducing production costs, adapting to large-scale continuous production, and ensuring conductivity.
Patent Information
- Application Number
- CN202511505057.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-21
- Publication Date
- 2025-11-18
- Estimated Expiration
- 2045-10-21
AI Technical Summary
In existing technologies, copper powder is easily oxidized during laser sintering, which leads to increased resistance of the conductive layer or loss of conductivity. Furthermore, the process must be carried out in a nitrogen or reducing atmosphere, which increases production costs and limits the openness and flexibility of the process, making it difficult to adapt to large-scale continuous production.
Conductive copper paste containing micron-sized copper powder, copper ligands, and solvent is used. Through laser sintering in an air atmosphere, the copper ligands undergo self-oxidation and reduction at the transient high temperature of the laser to generate nano-copper crystal nuclei, forming a dense and continuous metallurgical network that avoids oxidation and ensures conductivity.
It achieves efficient sintering in an air atmosphere, reduces production costs, is suitable for open continuous production, ensures the conductivity and structural stability of the conductive layer, and is suitable for industrial application.
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the field of printed electronics, and relates to a conductive copper paste and a laser sintering process thereof. BACKGROUND
[0002] In the field of printed electronics, the conductive performance and processing cost of metal interconnection lines are core concerns. Copper is the key conductive phase of low-silver / no-silver conductive paste due to its excellent conductivity and low cost advantage.
[0003] In the prior art, such as patent application CN119634731A, low-temperature laser sintering technology is applied to low-silver or no-silver conductive paste. By precisely controlling the laser frequency, power density and wavelength, efficient and uniform formation of the conductive layer is achieved at a lower temperature. This avoids the damage to the material structure caused by traditional high-temperature sintering and reduces the amount of silver used, thereby reducing production costs to some extent and providing a feasible path for the application of low-silver / no-silver conductive paste.
[0004] However, the above patent application still has a key technical bottleneck: in order to avoid the oxidation of the surface of the metal powder (especially copper powder) during the sintering process, sintering operation must be carried out in a nitrogen or reducing gas atmosphere. If there is no such atmosphere protection, a layer of copper oxide or cuprous oxide will quickly form on the surface of the copper powder. This oxide layer will significantly hinder the diffusion and migration of copper atoms, resulting in the inability to form effective sintering necks between copper particles, which in turn causes the resistance of the sintered conductive layer to increase significantly, and even lose the conductive function.
[0005] This limitation directly leads to practical application problems. On the one hand, the preparation, delivery and atmosphere control of nitrogen or reducing gas require additional special equipment, increasing the initial investment and operation and maintenance costs of the production line. On the other hand, the closed atmosphere environment limits the openness and flexibility of the process, making it difficult to adapt to large-scale, continuous open production scenarios, and restricting the industrialization promotion efficiency of low-silver / no-silver copper-based conductive paste in the field of printed electronics. SUMMARY
[0006] The purpose of the present application is to solve the problems existing in the prior art and provide a conductive copper paste and a laser sintering process thereof.
[0007] To achieve the above-mentioned purpose, the technical solutions adopted by the present application are as follows:
[0008] The conductive copper paste comprises micron copper powder, copper ligand (a copper-containing chemical substance or a combination thereof capable of being converted into metallic copper during laser sintering / heating) and solvent, wherein the content of the micron copper powder is not less than 50 wt%, and the content of the copper ligand is not less than 2 wt%; the copper ligand is formed by coordination of copper formate and amino ligand, the molar ratio of copper formate to amino ligand is 1:2-4; the amino ligand is one or more of hexylamine, 2-ethylhexylamine, butylamine, beta-alanine, glycine, 2-amino-2-methyl-1-propanol, octylamine and oleylamine, and the common feature of these amino ligands is that they can decompose to release reducing or neutral volatile products when heated.
[0009] As a preferred technical solution:
[0010] The conductive copper paste as described above, the content of the micron copper powder is not higher than 80 wt%, the content of the copper ligand is not higher than 10 wt%, and the mass ratio of the copper ligand to the solvent is 1:3-6.
[0011] The conductive copper paste as described above, the solvent is an organic solvent, the organic solvent is one or more of methanol, ethanol, ethylene glycol, ethylene glycol methyl ether and 1-methyl-2-pyrrolidone, the copper ligand and the organic solvent form a copper ligand solution, and the organic solvent is used to dissolve the copper ligand and adjust the dispersibility and viscosity of the paste.
[0012] The conductive copper paste as described above, the configuration step of the copper ligand solution comprises:
[0013] (a) grinding and mixing the copper formate and the amino ligand to obtain a mixed powder;
[0014] (b) adding the mixed powder into the organic solvent, slowly heating to a reaction temperature under stirring, and keeping the temperature to make the mixed powder completely dissolved, thereby obtaining the copper ligand solution.
[0015] In step (b) of the conductive copper paste as described above, the stirring speed is 200-1500 rpm, the heating rate is 0.5-3 ℃ / min, the reaction temperature is 90-120 ℃, and the holding time is 2-8 h.
[0016] The conductive copper paste as described above, the D50 particle size of the micron copper powder is 1-2 μm.
[0017] The conductive copper paste as described above further comprises an organic additive, the content of the organic additive is not more than 10 wt%, the organic additive is one or more of terpineol, dihydroterpineol, ethylene glycol butyl ether, diethylene glycol butyl ether, diethylene glycol butyl ether acetate, tributyl citrate, dibutyl phthalate, ethyl cellulose, cellulose acetate butyrate and acrylic resin, the organic additive mainly exists as a carrier, including a binder, a plasticizer and the like, and the core role is to enable the copper paste to be well printed, well film-formed, less defective, maintain structural stability before and after sintering, quickly remove during sintering, and as little residual as possible.
[0018] The application further provides a process for laser sintering of the conductive copper paste as described in any one of the above, after the conductive copper paste is printed on the surface of the substrate, sintering is performed in an air, nitrogen, inert gas (such as argon) or reducing gas atmosphere by using a picosecond or femtosecond pulse laser system, and during the sintering process, the surface of the sample is scanned by a multi-path scanning program controlled by software, wherein the wavelength of the laser is 1064 nm, the power is 0.1-10 W, the scanning rate is 10-200 mm / s, and the pulse frequency is 500-1000 kHz.
[0019] As a preferred technical solution:
[0020] The process as described above, the substrate includes a flexible substrate, a ceramic substrate, a glass substrate or an epoxy resin substrate, and the type of substrate is not limited and can be selected according to actual needs.
[0021] Principle of the application:
[0022] In the prior art, the core of laser sintering of the conductive copper paste is to use a high-energy laser beam to rapidly heat copper particles for transient heating, so that the copper particles reach the melting point or a temperature close to the melting point in a short time, and then realize metallurgical bonding between the particles. From the atomic level, after the copper particles in the conductive copper paste absorb laser energy, the surface temperature of the copper particles will rise sharply to several thousand degrees Celsius, forming a local high-temperature zone. Since the laser action time is extremely short, only femtoseconds to picoseconds, the heat does not have time to diffuse, which avoids the overall melting of the copper particles, and realizes the connection through surface melting or solid-state diffusion. Specifically, if the surface temperature of the copper particles exceeds the melting point, a liquid copper film will be formed on the surface, and atoms will migrate to the particle contact point (i.e. the neck) under the driving force of surface tension, forming a liquid phase bridge; if the temperature does not reach the melting point, solid copper atoms will migrate to the neck through surface diffusion, grain boundary diffusion or vacancy mechanism under thermal excitation, forming a solid-state connection. The radius of the neck increases exponentially with time, and its growth rate is affected by temperature, particle size and diffusion coefficient. In a high-temperature environment, the atomic diffusion rate increases, and the neck growth is also more rapid. With the continuous growth of the neck, the pores between the particles gradually decrease, and finally a dense metallurgical bonding body is formed.
[0023] The rapid heating characteristics of laser sintering enable copper particles to complete the connection in a solid or semi-solid state, effectively avoiding the problems of grain coarsening or oxidation caused by long-time high temperature in the traditional sintering process. However, this sintering mechanism cannot be carried out in air because copper will quickly form copper oxide (CuO) or cuprous oxide (Cu2O) on its surface when heated in air.
[0024] On the one hand, the oxide layer covers the surface of the copper particles, forming a dense barrier with a diffusion coefficient several orders of magnitude lower than that of pure copper, which directly leads to a decrease of more than 90% in the growth rate of the neck. On the other hand, the resistivity of the oxide layer is much higher than that of pure copper, which will block the current conduction path. Once the current conduction path is blocked, the current can only pass through the narrow metal contact points during the sintering process of the conductive copper paste, which will cause the resistivity to rise and even make the conductive copper paste completely lose its conductivity.
[0025] The laser sintering of the conductive copper paste of the present application can be carried out in any atmosphere of air, nitrogen, inert gas or reducing gas, and does not necessarily have to be carried out in nitrogen, inert gas or reducing gas, because:
[0026] Under the transient high temperature generated by the laser, the copper ligand undergoes a self-oxidation-reduction reaction. The amino ligand provides electrons to the copper ions in copper formate through a charge transfer mechanism, reducing them to zero-valent metallic copper, and rapidly generating nanometer copper crystal nuclei in situ under the transient high temperature of the laser. These nanometer copper crystal nuclei have extremely high surface energy and diffusion activity due to their extremely small particle size and large specific surface area, and are extremely prone to surface migration and agglomeration, which in turn causes the nanometer copper crystal nuclei to rapidly diffuse and agglomerate in the particle contact area to form an initial neck connection. As the laser continues to irradiate, the surface of the micron-sized copper powder melts locally, and under the bridging action of the nanometer copper crystal nuclei, the neck size gradually expands. Finally, the nanometer copper crystal nuclei and micron-sized copper powder jointly form a dense and continuous metallurgical network. During the entire process, the pyrolysis of the copper ligand and the amino ligand releases reducing or neutral volatile products such as carbon monoxide and amino radicals, which can form a local reducing / inert environment on the surface of the nanometer copper crystal nuclei and micron-sized copper powder, preventing the nanometer copper crystal nuclei and micron-sized copper powder from being oxidized on the surface during the sintering process, thereby jointly ensuring the smooth progress of the sintering process in air. In addition, the amino ligand is volatilized in the form of gas after thermal decomposition, leaving only a small amount of metallic copper and a trace amount of oxide, significantly reducing the influence of impurities on the conductivity.
[0027] The molar ratio of the copper formate without water to the amino ligand is controlled to be 1:2-4, so that the proportion of the organic components (formate and amino ligand) in the copper ligand is high, and the process of "absorption-reduction-removal" is ensured to proceed smoothly. If the proportion of the organic components is too small, the copper ligand cannot absorb enough laser energy, and the reaction is insufficient, so that the amount of reducing or neutral volatile products released in the decomposition process is insufficient, and an effective local reducing / inert environment cannot be formed on the surface of the particles, so that the sintering requirement in the air atmosphere cannot be met; if the proportion of the organic components is too high, excessive organic by-products and gas will be released in the decomposition process, which will cause the film layer to bubble, crack or have too much organic residue, and finally damage the density and conductivity of the film layer.
[0028] The content of the copper ligand in the conductive copper paste is controlled to be not less than 2wt%, because when the content of the copper ligand is too low, on the one hand, the gas and heat generated by the decomposition are insufficient to form a stable reaction environment on the surface of the particles, which hinders the reduction of copper ions and the formation of necks, thereby destroying the sintering conditions in the air atmosphere; on the other hand, it will reduce the densification degree of the material and cause poor printing stability.
[0029] The content of the micron-sized copper powder in the conductive copper paste is controlled to be not less than 50wt%, because when the content of the micron-sized copper powder is too low, the system lacks sufficient scattering and energy trapping effect, and cannot provide a stable energy environment for the decomposition and reduction of the copper ligand, so the nanometer copper crystal nucleus is easily oxidized by oxygen in the air, which makes it difficult to sinter in the air atmosphere.
[0030] The micron-sized copper powder in the conductive copper paste can also improve the utilization rate of laser energy, because the micron-sized copper powder has a high specific surface area structure, which can produce strong scattering and shielding effect, significantly reducing the transmittance of laser, and thereby enhancing the overall absorption capacity of the conductive copper paste to laser and the energy trapping effect. Specifically, the mechanism is as follows:
[0031] Firstly, in the film, the incident laser will not only be absorbed by the copper ligand, but also be strongly scattered by the micron-sized copper powder. After multiple scattering, the effective travel distance of the laser in the film is lengthened, so that the number of irradiation times of the copper ligand to the laser is increased.
[0032] Secondly, multiple scattering can reduce the straight-through energy of the laser and reduce the heat absorption of the substrate, so that the heat is mainly retained in the film layer. At the same time, the micron-sized copper powder has high thermal conductivity, which can homogenize the local temperature gradient on a microscale, which is beneficial to the uniform pyrolysis of the copper ligand and the synergistic densification.
[0033] The content of the micron-sized copper powder is controlled to be not less than 50wt%, which can also avoid the problems of under-firing and high square resistance caused by insufficient scattering effect and imperfect skeleton structure.
[0034] The laser sintering parameters (laser wavelength 1064 nm, power 0.1-10 W, pulse frequency 500-1000 kHz) of the present application match the optical properties of the conductive copper paste, forming a more fine parameter-structure-property coupling path, effectively supporting the large-scale application of industrial flexible circuits or electromagnetic shielding patterns. The essence of matching is to make the effective penetration depth δ and the film thickness t be of the same order of magnitude, while the energy per unit length is lower than the damage threshold across the "copper ligand decomposition / nucleation + particle neck growth" thermal threshold. The laser with a wavelength of 1064 nm matches the NIR absorption band of the copper ligand, the micron-sized copper powder enhances scattering and reduces transmittance, and amplifies thermal deposition. If any of the wavelength, power, and pulse frequency is too large or too small, it will affect the energy absorption effect, destroy the air sintering conditions, cause oxidation, and cannot be sintered in air, which will also push the system into the failure zone of "only sintering the surface layer / under-sintering / over-sintering", resulting in increased square resistance, increased porosity / cracking, or substrate damage.
[0035] Advantages:
[0036] (1) The conductive copper paste of the present application contains micron-sized copper powder, copper ligand and solvent, and can be sintered in air atmosphere by matching with a specific laser sintering process, without relying on nitrogen or reducing gas protection. This solves the problem of additional configuration of atmosphere control equipment in the prior art, increases production cost, and restricts the openness of the process and large-scale continuous production in a closed atmosphere. It reduces the production line investment and operation cost, adapts to open and continuous production scenarios, and is beneficial to industrialization.
[0037] (2) By controlling the composition and content of the copper ligand, it can be self-oxidized and reduced to form a nanometer copper crystal nucleus at a laser transient high temperature, and assist the micron-sized copper powder to form a dense and continuous metallurgical network. It can also release reducing or neutral volatile products to form a local reducing / inert environment on the surface of the copper powder and nanometer copper crystal nucleus, effectively preventing the oxidation of copper during the sintering process, avoiding the problem of oxidation layer hindering the diffusion of copper atoms, leading to the increase of the resistance of the conductive layer or the loss of the conductive function, and ensuring the conductive performance of the copper film after air sintering.
[0038] (3) The content of micron-sized copper powder is not less than 50wt%, which can enhance the absorption capacity and energy retention effect of the copper paste to the laser, reduce the heat absorption of the substrate and homogenize the local temperature gradient, assist the uniform pyrolysis and synergistic densification of the copper ligand, avoid the problem of under-sintering and square resistance increase caused by insufficient scattering effect and imperfect skeleton structure, and further ensure the conductive and structural performance of the copper film. DETAILED DESCRIPTION
[0039] The application will be further described below with reference to the specific embodiments. It should be understood that these embodiments are only used to illustrate the application and not to limit the scope of the application. Furthermore, it should be understood that those skilled in the art can make various modifications or changes to the application after reading the content of the application, and these equivalent forms also fall within the scope defined by the appended claims.
[0040] The following are the test methods of the relevant performance indicators in each example and comparative example. All indicator test processes are carried out in parallel for 10 times, and the average value is taken as the final test result:
[0041] Sheet resistance, sheet resistance change rate after baking at 200℃ for 2h, sheet resistance change rate after exposure in air for 720h: sheet resistance is tested by using ST2258C digital four-probe tester, test current is 10mA, test voltage range is 0-200mV, probe spacing is 2mm; test environmental conditions: temperature is 25±2℃, relative humidity is 60±5%; sheet resistance change rate calculation formula is: sheet resistance change rate=[(treated sheet resistance-initial sheet resistance) / initial sheet resistance]×100%, the treated sheet resistance refers to the sheet resistance after baking at 200℃ for 2h or the sheet resistance after exposure in air for 720h;
[0042] Electromagnetic shielding effectiveness under 5.5GHz frequency band: refer to GB / T 12190-2006, use a vector network analyzer (Agilent N5247A) with a coaxial transmission line test fixture for testing, record the reflection coefficient and transmission coefficient at the 5.5GHz point, and then calculate the electromagnetic shielding effectiveness according to the calculation method specified in the standard.
[0043] Example 1
[0044] A laser sintering process of conductive copper paste, the specific steps are as follows:
[0045] (1) Preparation of materials;
[0046] Copper formate anhydrous;
[0047] Amino ligand: hexylamine;
[0048] Organic solvent: methanol;
[0049] Micron-sized copper powder: D50 particle size is 1μm;
[0050] Organic additive: terpineol, CAS number is 8000-41-7;
[0051] Substrate: PET flexible substrate, manufacturer is DuPont Company, brand is Melinex ST506, thickness is 0.125mm;
[0052] (2) Preparation of copper ligand solution;
[0053] (a) grinding and mixing anhydrous copper formate with an amino ligand to obtain a mixed powder;
[0054] (b) adding the mixed powder into an organic solvent, slowly increasing the temperature to a reaction temperature under stirring, and keeping the temperature, so that the mixed powder is completely dissolved, to obtain a copper ligand solution;
[0055] In step (a), the molar ratio of anhydrous copper formate to the amino ligand is 1:2; in step (b), the stirring speed is 200 rpm, the temperature increasing rate is 0.5℃ / min, the reaction temperature is 90℃, the keeping time is 2h, and the mass ratio of the mixed powder to the organic solvent is 1:3;
[0056] (3) preparing a conductive copper paste;
[0057] The conductive copper paste is composed of micron copper powder, the copper ligand solution and an organic additive; in the conductive copper paste, the content of the micron copper powder is 50wt%, the content of the copper ligand solution is 40wt%, and the content of the organic additive is 10wt%; it is calculated that the content of the copper ligand in the conductive copper paste is 10wt%;
[0058] (4) laser sintering;
[0059] After the conductive copper paste is printed on the surface of the substrate, the paste is sintered in an air atmosphere by using a picosecond pulse laser system to form a copper film with a thickness of 0.05mm on the substrate, to obtain a copper-clad substrate; in the sintering process, the sample surface is scanned by a multi-path scanning program controlled by software, wherein the spot diameter is 30μm, the scanning interval is 15μm, the number of repeated scanning is 3, the laser wavelength is 1064nm, the power is 0.1W, the scanning rate is 10mm / s, and the pulse frequency is 500kHz.
[0060] Tests show that the sheet resistance of the copper film is 15mΩ / □, the sheet resistance change rate of the copper film is 3% after being baked at 200℃ for 2h, and the sheet resistance change rate of the copper film is 7% after being exposed to air for 720h; the electromagnetic shielding effectiveness of the copper-clad substrate at a frequency of 5.5GHz is 35dB.
[0061] Example 2
[0062] A laser sintering process of a conductive copper paste, the specific steps are as follows:
[0063] (1) preparation of materials;
[0064] anhydrous copper formate;
[0065] amino ligand: a mixture of 2-ethylhexylamine and butylamine with a molar ratio of 1:3;
[0066] organic solvent: a mixture of ethanol and ethylene glycol methyl ether with a molar ratio of 1:4;
[0067] Micron copper powder: D50 particle size is 1.5 μm;
[0068] Organic additive: diethylene glycol butyl ether acetate;
[0069] Substrate: ceramic substrate, manufacturer is Kyocera Corporation, mainly made of alumina (alumina mass ratio is 96%), thickness is 0.635 mm;
[0070] (2) configuring copper ligand solution;
[0071] (a) grinding and mixing copper formate anhydrous and amino ligand to obtain mixed powder;
[0072] (b) adding the mixed powder into organic solvent, slowly heating to reaction temperature under stirring condition and keeping, so that the mixed powder is completely dissolved, and the copper ligand solution is obtained;
[0073] In step (a), the molar ratio of copper formate anhydrous to amino ligand is 1:3; in step (b), the stirring speed is 800 rpm, the heating rate is 1 ℃ / min, the reaction temperature is 110 ℃, the keeping time is 5 h, and the mass ratio of mixed powder to organic solvent is 1:4;
[0074] (3) configuring conductive copper paste;
[0075] The conductive copper paste is composed of micron copper powder, copper ligand solution and organic additive; in the conductive copper paste, the content of micron copper powder is 65 wt%, the content of copper ligand solution is 30 wt%, and the content of organic additive is 5 wt%; it is calculated that the content of copper ligand in the conductive copper paste is 6 wt%;
[0076] (4) laser sintering;
[0077] After the conductive copper paste is printed on the surface of the substrate, sintering is carried out under nitrogen atmosphere by using femtosecond pulse laser system to form a copper film with a thickness of 0.03 mm on the substrate, and a copper-clad substrate is obtained; in the sintering process, the sample surface is scanned by multiple paths through software control of laser scanning program, wherein the spot diameter is 30 μm, the scanning pitch is 15 μm, the repeated scanning number is 2, the laser wavelength is 1064 nm, the power is 5 W, the scanning rate is 100 mm / s, and the pulse frequency is 800 kHz.
[0078] Tests show that the sheet resistance of the copper film is 8 mΩ / □, the sheet resistance change rate of the copper film is 2% after 200 ℃ baking for 2 h, and the sheet resistance change rate of the copper film is 6% after exposure to air for 720 h; the electromagnetic shielding effectiveness of the copper-clad substrate under 5.5 GHz frequency band is 40 dB.
[0079] Example 3
[0080] A laser sintering process of conductive copper paste, the specific steps are as follows:
[0081] (1) Preparation of materials;
[0082] Copper formate anhydrous;
[0083] Amino ligand: mixture of β-alanine and glycine with a molar ratio of 1:4;
[0084] Organic solvent: 1-methyl-2-pyrrolidone;
[0085] Micron copper powder: D50 particle size is 1.2 μm;
[0086] Organic additive: acrylic resin, CAS number 9003-01-4;
[0087] Substrate: glass substrate, manufacturer is Corning Company, brand is EAGLE XG, thickness is 0.7 mm;
[0088] (2) Preparation of copper ligand solution;
[0089] (a) Mix copper formate anhydrous and amino ligand to obtain mixed powder;
[0090] (b) After adding the mixed powder into the organic solvent, slowly heat to the reaction temperature under stirring condition and keep the temperature, so that the mixed powder is completely dissolved, and the copper ligand solution is obtained;
[0091] In step (a), the molar ratio of copper formate anhydrous to amino ligand is 1:4; in step (b), the stirring speed is 1500 rpm, the heating rate is 3 ℃ / min, the reaction temperature is 120 ℃, the holding time is 8 h, and the mass ratio of mixed powder to organic solvent is 1:6;
[0092] (3) Preparation of conductive copper paste;
[0093] The conductive copper paste is composed of micron copper powder, copper ligand solution and organic additive; in the conductive copper paste, the content of micron copper powder is 80 wt%, the content of copper ligand solution is 15 wt%, and the content of organic additive is 5 wt%; it is calculated that the content of copper ligand in the conductive copper paste is 2.1 wt%;
[0094] (4) Laser sintering;
[0095] After the conductive copper paste is printed on the surface of the substrate, a picosecond pulsed laser system is used for sintering in an air atmosphere to form a copper film with a thickness of 0.02 mm on the substrate to obtain a copper-clad substrate; during the sintering process, the sample surface is scanned by a multi-path scanning program controlled by software, wherein the spot diameter is 25 μm, the scanning pitch is 12 μm, the number of repeated scanning is 2, the laser wavelength is 1064 nm, the power is 10 W, the scanning rate is 200 mm / s, and the pulse frequency is 1000 kHz.
[0096] Tests show that the sheet resistance of the copper film is 5 mΩ / □, the sheet resistance change rate of the copper film is 5% after baking at 200 ℃ for 2 h, and the sheet resistance change rate of the copper film is 10% after exposure to air for 720 h; the electromagnetic shielding effectiveness of the copper-clad substrate at a frequency band of 5.5 GHz is 30 dB.
[0097] Example 4
[0098] A laser sintering process of a conductive copper paste, the specific steps are as follows:
[0099] (1) Preparation of materials;
[0100] Copper formate anhydrous;
[0101] Amino ligand: a mixture of 2-amino-2-methyl-1-propanol and octylamine with a molar ratio of 1:2.5;
[0102] Organic solvent: a mixture of ethylene glycol and ethanol with a molar ratio of 1:5;
[0103] Micron-sized copper powder: D50 particle size is 1.8 μm;
[0104] Organic additive: dibutyl phthalate;
[0105] Substrate: PI flexible substrate, manufacturer is DuPont Company, model is Kapton HN, thickness is 0.05 mm;
[0106] (2) Preparation of copper ligand solution;
[0107] (a) Grind and mix copper formate anhydrous and amino ligand to obtain a mixed powder;
[0108] (b) After the mixed powder is added to the organic solvent, slowly heat to the reaction temperature under stirring conditions and keep the temperature, so that the mixed powder is completely dissolved, and the copper ligand solution is obtained;
[0109] In step (a), the molar ratio of copper formate anhydrous to amino ligand is 1:2.5; in step (b), the stirring speed is 500 rpm, the heating rate is 2 ℃ / min, the reaction temperature is 100 ℃, the holding time is 4 h, and the mass ratio of the mixed powder to the organic solvent is 1:5;
[0110] (3) configuring conductive copper paste;
[0111] The conductive copper paste is composed of micron copper powder, copper ligand solution and organic additive; in the conductive copper paste, the content of micron copper powder is 70wt%, the content of copper ligand solution is 25wt%, and the content of organic additive is 5wt%; it is calculated that the content of copper ligand in the conductive copper paste is 4.2wt%;
[0112] (4) laser sintering;
[0113] After the conductive copper paste is printed on the surface of the substrate, sintering is performed on the substrate by using a femtosecond pulse laser system in an air atmosphere to form a copper film with a thickness of 0.04mm on the substrate, thereby obtaining a copper-clad substrate; in the sintering process, the surface of the sample is scanned by multiple paths through software control of the laser scanning program, wherein the spot diameter is 30μm, the scanning pitch is 20μm, the number of repeated scanning is 3, the laser wavelength is 1064nm, the power is 3W, the scanning rate is 20mm / s, and the pulse frequency is 600kHz.
[0114] Tests show that the square resistance of the copper film is 12mΩ / □, the square resistance change rate of the copper film is 4.5% after baking at 200℃ for 2h, and the square resistance change rate of the copper film is 8% after exposure to air for 720h; the electromagnetic shielding effectiveness of the copper-clad substrate at a frequency band of 5.5GHz is 33dB.
[0115] Example 5
[0116] A laser sintering process of a conductive copper paste, the specific steps are as follows:
[0117] (1) preparation of materials;
[0118] copper formate anhydrous;
[0119] amino ligand: a mixture of oleylamine and octylamine with a molar ratio of 1:5;
[0120] organic solvent: ethylene glycol butyl ether;
[0121] micron copper powder: D50 particle size is 2μm;
[0122] organic additive: ethyl cellulose, CAS number is 9004-57-3;
[0123] substrate: FR-4 epoxy resin substrate, manufacturer is Jiangtao Multilayer Board Holding Co., Ltd., thickness is 1mm;
[0124] (2) configuration of copper ligand solution;
[0125] (a) grinding and mixing copper formate anhydrous and amino ligand to obtain a mixed powder;
[0126] (b) after the mixed powder is added into the organic solvent, the mixed powder is completely dissolved by slowly increasing the temperature to the reaction temperature and keeping the temperature under stirring, to obtain a copper ligand solution;
[0127] In step (a), the molar ratio of copper formate to the amino ligand is 1:3.5; in step (b), the stirring speed is 1000 rpm, the temperature increasing rate is 1.5℃ / min, the reaction temperature is 95℃, the keeping time is 6h, and the mass ratio of the mixed powder to the organic solvent is 1:5;
[0128] (3) preparing a conductive copper paste;
[0129] The conductive copper paste is composed of the micron copper powder, the copper ligand solution and the organic additive; in the conductive copper paste, the content of the micron copper powder is 75wt%, the content of the copper ligand solution is 20wt%, and the content of the organic additive is 5wt%; it is calculated that the content of the copper ligand in the conductive copper paste is 3.3wt%;
[0130] (4) laser sintering;
[0131] After the conductive copper paste is printed on the surface of the substrate, the paste is sintered by using a picosecond pulsed laser system under an argon atmosphere to form a copper film with a thickness of 0.02mm on the substrate, to obtain a copper-clad substrate; in the sintering process, the sample surface is scanned by a multi-path scanning program controlled by software, wherein the spot diameter is 25μm, the scanning interval is 10μm, the number of repeated scanning is 2, the laser wavelength is 1064nm, the power is 8W, the scanning speed is 150mm / s, and the pulse frequency is 900kHz.
[0132] Tests show that the sheet resistance of the copper film is 7mΩ / □, the sheet resistance change rate of the copper film is 3% after being baked at 200℃ for 2h, and the sheet resistance change rate of the copper film is 8% after being exposed to air for 720h; the electromagnetic shielding effectiveness of the copper-clad substrate at a frequency of 5.5GHz is 32dB.
[0133] Example 6
[0134] A laser sintering process of a conductive copper paste, the specific steps are as follows:
[0135] (1) preparation of materials;
[0136] copper formate;
[0137] amino ligand: a mixture of 2-ethylhexylamine and butylamine with a molar ratio of 1:4;
[0138] organic solvent: 1-methyl-2-pyrrolidone;
[0139] micron copper powder: D50 particle size is 1.41μm;
[0140] Organic additive: mixture of dihydroterpineol, ethylene glycol monobutyl ether and diethylene glycol monobutyl ether in a molar ratio of 1:1:1;
[0141] Substrate: PET flexible substrate, brand Melinex ST506, thickness 0.125mm, manufacturer DuPont;
[0142] (2) configuring copper ligand solution;
[0143] (a) grinding and mixing copper formate anhydrous and amino ligand to obtain mixed powder;
[0144] (b) adding the mixed powder into organic solvent, slowly heating to reaction temperature under stirring condition and keeping, so that the mixed powder is completely dissolved, and copper ligand solution is obtained;
[0145] In step (a), the molar ratio of copper formate anhydrous and amino ligand is 1:2; in step (b), the stirring speed is 600rpm, the heating rate is 2.5℃ / min, the reaction temperature is 120℃, the keeping time is 6h, and the mass ratio of mixed powder and organic solvent is 1:4;
[0146] (3) configuring conductive copper paste;
[0147] The conductive copper paste is composed of micron copper powder, copper ligand solution and organic additive; in the conductive copper paste, the content of micron copper powder is 60wt%, the content of copper ligand solution is 35wt%, and the content of organic additive is 5wt%; by calculation, the content of copper ligand in the conductive copper paste is 7wt%;
[0148] (4) laser sintering;
[0149] After printing the conductive copper paste on the surface of the substrate, sintering is carried out by using picosecond pulse laser system in air atmosphere, and copper film with a thickness of 0.04mm is formed on the substrate to obtain copper-clad substrate; in the sintering process, the sample surface is scanned by multiple paths through software control of laser scanning program, wherein the spot diameter is 35μm, the scanning interval is 15μm, the repeated scanning number is 3, the laser wavelength is 1064nm, the power is 6W, the scanning rate is 80mm / s, and the pulse frequency is 700kHz.
[0150] Tests show that the sheet resistance of the copper film is 10mΩ / □, the sheet resistance change rate of the copper film is 5% after baking at 200℃ for 2h, and the sheet resistance change rate of the copper film is 11% after exposure to air for 720h; the electromagnetic shielding effectiveness of the copper-clad substrate under 5.5GHz frequency band is 35dB.
[0151] Example 7
[0152] A laser sintering process of a conductive copper paste, the specific steps are as follows:
[0153] (1) Preparation of materials;
[0154] Anhydrous copper formate;
[0155] Amino ligand: mixture of 2-amino-2-methyl-1-propanol and octylamine with a molar ratio of 1:3;
[0156] Organic solvent: ethylene glycol butyl ether;
[0157] Micron-sized copper powder: D50 particle size of 1.65 μm;
[0158] Organic additive: mixture of tributyl citrate and cellulose acetate butyrate (CAS No. 9004-36-8) with a mass ratio of 1:1;
[0159] Substrate: glass substrate, manufacturer: Corning, brand: EAGLE XG, thickness: 0.7 mm;
[0160] (2) Preparation of copper ligand solution;
[0161] (a) Grinding and mixing anhydrous copper formate and amino ligand to obtain a mixed powder;
[0162] (b) After adding the mixed powder into the organic solvent, slowly increasing the temperature to the reaction temperature under stirring and keeping the temperature, so that the mixed powder is completely dissolved, thereby obtaining the copper ligand solution;
[0163] In step (a), the molar ratio of anhydrous copper formate to amino ligand is 1:4; in step (b), the stirring speed is 1200 rpm, the heating rate is 1.2 ℃ / min, the reaction temperature is 105 ℃, the keeping time is 3 h, and the mass ratio of the mixed powder to the organic solvent is 1:5;
[0164] (3) Preparation of conductive copper paste;
[0165] The conductive copper paste is composed of micron-sized copper powder, copper ligand solution and organic additive; in the conductive copper paste, the content of micron-sized copper powder is 70 wt%, the content of copper ligand solution is 25 wt%, and the content of organic additive is 5 wt%; by calculation, the content of copper ligand in the conductive copper paste is 4.2 wt%;
[0166] (4) Laser sintering;
[0167] After the conductive copper paste is printed on the surface of the substrate, a copper film with a thickness of 0.02 mm is formed on the substrate by sintering in an air atmosphere using a femtosecond pulse laser system to obtain a copper-clad substrate; during the sintering process, the surface of the sample is scanned by a multi-path scanning program controlled by software, wherein the spot diameter is 25 μm, the scanning pitch is 10 μm, the number of repeated scanning is 1, the laser wavelength is 1064 nm, the power is 9 W, the scanning rate is 160 mm / s, and the pulse frequency is 850 kHz.
[0168] Tests show that the sheet resistance of the copper film is 14 mΩ / □, the sheet resistance change rate of the copper film is 3.8% after baking at 200 ℃ for 2 h, and the sheet resistance change rate of the copper film is 5% after exposure to air for 720 h; the electromagnetic shielding effectiveness of the copper-clad substrate at a frequency band of 5.5 GHz is 38 dB.
[0169] Comparative Example 1
[0170] A laser sintering process of a conductive copper paste, which is different from Example 1 in that: when the conductive copper paste is configured, the amount of micron-sized copper powder added is reduced, and the reduced part of the micron-sized copper powder is replaced with an equal amount of organic solvent, and the content of micron-sized copper powder in the conductive copper paste is 45 wt%.
[0171] Tests show that the sheet resistance of the copper film is 19 mΩ / □, the sheet resistance change rate of the copper film is 7% after baking at 200 ℃ for 2 h, and the sheet resistance change rate of the copper film is 12% after exposure to air for 720 h; the electromagnetic shielding effectiveness of the copper-clad substrate at a frequency band of 5.5 GHz is 28 dB.
[0172] Compared with Comparative Example 1 and Example 1, the performance indicators of the copper film and the copper-clad substrate are obviously poorer, which is because the amount of micron-sized copper powder added is too low. On the one hand, the system lacks sufficient scattering and energy trapping effect, which cannot provide stable conditions for the decomposition and reduction of copper ligands, leading to the rapid oxidation of nanometer copper crystal nucleus by oxygen in the air, which destroys the sintering conditions in the air atmosphere. On the other hand, the scattering effect is insufficient and the skeleton structure is imperfect, which causes under-sintering and sheet resistance increase, and at the same time, the utilization rate of laser energy by micron-sized copper powder decreases, the densification degree of the film layer is insufficient, and finally the performance indicators are poor.
[0173] Comparative Example 2
[0174] A laser sintering process of a conductive copper paste, which is different from Example 1 in that: in step (a), the molar ratio of copper formate to amino ligand is 1:1.
[0175] Tests show that the sheet resistance of the copper film is 22 mΩ / □, the sheet resistance change rate of the copper film is 6% after baking at 200 ℃ for 2 h, and the sheet resistance change rate of the copper film is 14% after exposure to air for 720 h; the electromagnetic shielding effectiveness of the copper-clad substrate at a frequency band of 5.5 GHz is 25 dB.
[0176] Compared with Example 1, the performance indicators of the copper film and the copper-clad substrate of Comparative Example 2 are obviously poor. This is because the proportion of the organic component in the copper ligand is insufficient, so that the copper ligand cannot absorb enough laser energy, the reaction is insufficient, the number of reducing or neutral volatile products released in the decomposition process is insufficient, an effective local reducing / inert environment cannot be formed on the surface of the particles, the air sintering condition is destroyed, the copper particles are easily oxidized and the neck growth is hindered, the denseness and conductivity of the film layer are reduced, and then the performance is poor.
[0177] Comparative Example 3
[0178] A laser sintering process of conductive copper paste, and the difference from Example 3 is that in step (a), the molar ratio of copper formate to amino ligand is 1:5.
[0179] Tests show that the sheet resistance of the copper film is 18 mΩ / □, the sheet resistance change rate of the copper film after baking at 200°C for 2h is 11%, and the sheet resistance change rate of the copper film after exposure to air for 720h is 20%; the electromagnetic shielding effectiveness of the copper-clad substrate at the frequency band of 5.5GHz is 23dB.
[0180] Compared with Example 3, the performance indicators of the copper film and the copper-clad substrate of Comparative Example 3 are obviously poor. This is because the proportion of the organic component in the copper ligand is too high, which will release excessive organic by-products and gas during the decomposition process, resulting in film layer bubbling, cracking or excessive residue, which destroys the denseness of the film layer, and at the same time, excessive impurities will also affect the conductivity, and excessive gas may interfere with the normal growth and metallurgical bonding of the neck, ultimately deteriorating the performance indicators.
[0181] Comparative Example 4
[0182] A laser sintering process of conductive copper paste, and the difference from Example 1 is that in step (4), the wavelength of the laser is 1065nm.
[0183] Tests show that the sheet resistance of the copper film is 16 mΩ / □, the sheet resistance change rate of the copper film after baking at 200°C for 2h is 8%, and the sheet resistance change rate of the copper film after exposure to air for 720h is 13.5%; the electromagnetic shielding effectiveness of the copper-clad substrate at the frequency band of 5.5GHz is 26dB.
[0184] Compared with Example 1, the performance indicators of the copper film and the copper-clad substrate of Comparative Example 4 are obviously poor. This is because the laser wavelength is shifted to 1065 nm, the wavelength mismatch causes the NIR absorption band of the copper ligand to be unable to effectively match, the scattering of the micron-sized copper powder is enhanced, and the amplification effect of thermal deposition is weakened, so that the effective penetration depth and the film thickness are no longer of the same order of magnitude, the energy per unit length is difficult to accurately cross the thermal threshold of “copper ligand decomposition / nucleation + particle neck growth”, which cannot guarantee that the sintering reaction is fully carried out, and may cause copper particles to be oxidized, resulting in performance degradation such as an increase in sheet resistance and a decrease in shielding effectiveness.
[0185] Comparative Example 5
[0186] A laser sintering process of conductive copper paste, and the difference from Example 1 is that in step (4), the laser wavelength is 1063 nm.
[0187] Tests show that the sheet resistance of the copper film is 17 mΩ / □, the sheet resistance change rate of the copper film after baking at 200°C for 2h is 4%, and the sheet resistance change rate of the copper film after exposure to air for 720h is 11%; the electromagnetic shielding effectiveness of the copper-clad substrate at the 5.5GHz frequency band is 30dB.
[0188] Compared with Example 1, the performance indicators of the copper film and the copper-clad substrate of Comparative Example 5 are obviously poor. This is because the laser wavelength is shifted to 1063 nm, the wavelength mismatch causes the NIR absorption band of the copper ligand to be unable to effectively match, the scattering of the micron-sized copper powder is enhanced, and the amplification effect of thermal deposition is weakened, so that the effective penetration depth and the film thickness are no longer of the same order of magnitude, the energy per unit length is difficult to accurately cross the thermal threshold of “copper ligand decomposition / nucleation + particle neck growth”, which cannot guarantee that the sintering reaction is fully carried out, and may cause copper particles to be oxidized, resulting in performance degradation such as an increase in sheet resistance and a decrease in shielding effectiveness.
[0189] Comparative Example 6
[0190] A laser sintering process of conductive copper paste, and the difference from Example 1 is that in step (4), the power is 0.05W.
[0191] Tests show that the sheet resistance of the copper film is 25 mΩ / □, the sheet resistance change rate of the copper film after baking at 200°C for 2h is 10%, and the sheet resistance change rate of the copper film after exposure to air for 720h is 12%; the electromagnetic shielding effectiveness of the copper-clad substrate at the 5.5GHz frequency band is 29dB.
[0192] Compared with Example 1, the performance indicators of the copper film and the copper-clad substrate of Comparative Example 6 are obviously poor, because the laser power is too low, so that the energy per unit length does not reach the thermal threshold of "copper ligand decomposition / nucleation + particle neck growth", and the insufficient energy leads to insufficient decomposition and reduction of copper ligands, low generation and low activity of nanometer copper nuclei, and difficult effective melting of the surface of the micron copper powder, slow and insufficient neck growth, and low densification degree of the film layer; at the same time, the insufficient release of reducing volatile products cannot resist oxidation, which finally causes performance degradation problems such as significant increase of square resistance and decrease of shielding effectiveness.
[0193] Comparative Example 7
[0194] A laser sintering process of conductive copper paste, and the difference from Example 3 is that in step (4), the power is 12 W.
[0195] Tests show that the square resistance of the copper film is 16 mΩ / □, the square resistance change rate of the copper film after baking at 200℃ for 2h is 8%, and the square resistance change rate of the copper film after exposure to air for 720h is 15%; the electromagnetic shielding effectiveness of the copper-clad substrate at the frequency band of 5.5GHz is 26dB.
[0196] Compared with Example 3, the performance indicators of the copper film and the copper-clad substrate of Comparative Example 7 are obviously poor, because the laser power is too high, which leads to the energy per unit length exceeding the damage threshold of the system, and the excessive energy not only causes excessive decomposition of copper ligands and violent volatilization of organic components, which leads to film layer bubbling and cracking, but also may cause excessive melting or grain coarsening of copper particles, and even damage the substrate; at the same time, the excessive energy may destroy the stability of the local reduction / inert environment, aggravate impurity residues, and finally make the conductivity, stability and shielding effectiveness of the copper film all obviously decrease.
[0197] Comparative Example 8
[0198] A laser sintering process of conductive copper paste, and the difference from Example 1 is that in step (4), the pulse frequency is 400 kHz.
[0199] Tests show that the square resistance of the copper film is 20 mΩ / □, the square resistance change rate of the copper film after baking at 200℃ for 2h is 6%, and the square resistance change rate of the copper film after exposure to air for 720h is 13%; the electromagnetic shielding effectiveness of the copper-clad substrate at the frequency band of 5.5GHz is 27dB.
[0200] Compared with Example 1, the copper film and the copper-clad substrate of Comparative Example 8 have significantly poorer performance indicators, because the pulse frequency is too low. On the one hand, the low-frequency pulse cannot provide a sustained and sufficient transient high-temperature environment for the copper ligand, resulting in incomplete decomposition of the copper ligand, blocked charge transfer reaction of the amino ligand, insufficient generation of nanometer copper crystal nuclei and uneven dispersion, and difficulty in effectively bridging the micron-sized copper powder to form a neck connection. On the other hand, the discontinuous energy input of the low-frequency pulse causes large local temperature fluctuations in the film layer, which cannot maintain a stable local reduction / inert environment, leading to easy oxidation of copper particles and hindering the uniform growth and densification of the neck, ultimately causing performance degradation problems such as increased sheet resistance and decreased shielding effectiveness.
[0201] Comparative Example 9
[0202] A laser sintering process of conductive copper paste, which is different from Example 3 in that the pulse frequency in step (4) is 1100 kHz.
[0203] Tests show that the sheet resistance of the copper film is 15 mΩ / □, the sheet resistance change rate of the copper film is 7% after baking at 200°C for 2h, and the sheet resistance change rate of the copper film is 14% after exposure to air for 720h; the electromagnetic shielding effectiveness of the copper-clad substrate at a frequency of 5.5GHz is 24dB.
[0204] Compared with Example 3, the copper film and the copper-clad substrate of Comparative Example 9 have significantly poorer performance indicators, because the pulse frequency is too high, resulting in too high overlap of laser pulses and excessive energy accumulation per unit time. The high-frequency pulse causes the thermal effects of adjacent pulses to overlap, forming a local overheating area, which not only causes excessive pyrolysis of the copper ligand, releasing a large amount of organic by-products and gas, and causing film layer blistering and cracking, but also causes excessive melting of the micron-sized copper powder surface and grain coarsening, damaging the microstructure of the copper film. At the same time, the overheating environment can accelerate the volatilization of the amino ligand that does not participate in the charge transfer reaction, weaken its reducing protection effect, and excessive energy can damage the surface of the substrate, further deteriorating the conductivity and stability of the copper film, ultimately leading to a significant decrease in performance indicators.
Claims
1. A conductive copper paste, characterized in that, It contains micron-sized copper powder, copper ligands, and solvent; wherein the content of micron-sized copper powder is not less than 50 wt%, and the content of copper ligands is not less than 2 wt%; the copper ligands are formed by coordination of anhydrous copper formate with amino ligands, and the molar ratio of anhydrous copper formate to amino ligands is 1:2-4; the amino ligands are one or more of hexylamine, 2-ethylhexylamine, butylamine, β-alanine, glycine, 2-amino-2-methyl-1-propanol, octylamine, and oleylamine.
2. The conductive copper paste according to claim 1, characterized in that, The content of micron-sized copper powder is no more than 80 wt%, the content of copper ligands is no more than 10 wt%, and the mass ratio of copper ligands to solvent is 1:3-6.
3. The conductive copper paste according to claim 1, characterized in that, The solvent is an organic solvent, and the copper ligand and the organic solvent together form a copper ligand solution.
4. The conductive copper paste according to claim 3, characterized in that, The preparation steps for the copper ligand solution include: (a) Anhydrous copper formate and amino ligands are ground and mixed to obtain a mixed powder; (b) After adding the mixed powder to the organic solvent, the mixture is heated to the reaction temperature and kept at that temperature under stirring to completely dissolve the mixed powder, thus obtaining the copper ligand solution.
5. The conductive copper paste according to claim 4, characterized in that, In step (b), the stirring speed is 200-1500 rpm, the heating rate is 0.5-3℃ / min, the reaction temperature is 90-120℃, and the holding time is 2-8h.
6. The conductive copper paste according to claim 1, characterized in that, The D50 particle size of micron-sized copper powder is 1-2 μm.
7. The conductive copper paste according to claim 1, characterized in that, It also contains organic additives, the content of which is no more than 10 wt%. The organic additives are one or more of the following: terpineol, dihydroterpineol, ethylene glycol butyl ether, diethylene glycol butyl ether, diethylene glycol butyl ether acetate, tributyl citrate, dibutyl phthalate, ethyl cellulose, cellulose acetate butyrate, and acrylic resin.
8. The laser sintering process for a conductive copper paste as described in any one of claims 1 to 7, characterized in that, After conductive copper paste is printed on the surface of the substrate, it is sintered in an atmosphere of air, nitrogen, inert gas or reducing gas using a picosecond or femtosecond pulsed laser system. During the sintering process, the laser scanning program is controlled by software to perform multi-path scanning on the sample surface. The laser wavelength is 1064nm, the power is 0.1-10W, and the pulse frequency is 500-1000kHz.
9. The process according to claim 8, characterized in that, The substrate includes flexible substrates, ceramic substrates, glass substrates, or epoxy resin substrates.
Citation Information
Patent Citations
Conductive paste low-temperature laser sintering method and application thereof
CN119634731A
Copper soldering paste and preparation method and application thereof
CN114799613A
High-temperature-resistant nano-copper for laser direct writing and preparation method and application of high-temperature-resistant nano-copper
CN118437937A
Composite ink for laser-induced selective copper metallization and process method
CN118496706A
Wiring board manufacturing method, wiring board and dispersion liquid for manufacturing wiring board
JP5859075B1
